Pengaruh Kompetensi Auditor, Ancaman Independensi dan Etika Profesi Terhadap Audit Judgment: Perspektif Dari Kantor Akuntan Publik di Jakarta Selatan - Muhammad Rizqi Deandra; Slamet Wahyudi (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the effect of auditor competence, independence threats, and professional ethics on audit judgment. This research is classified as quantitative research. The data collection method used is primary data through a field survey. The technique employed involves distributing questionnaires to 106 external auditor respondents working at Public Accounting Firms in the South Jakarta area. The sampling method used is non-probability sampling with a purposive sampling technique. The data analysis in this study was processed using SPSS version 25. The results of this study show that, partially, auditor competence has a significant effect and positive effect on audit judgment, independence threats have a negative and significant effect on audit judgment, and professional ethics have a positive and significant effect on audit judgment.